Optimalisasi Manajemen Risiko dalam Pengembangan Aplikasi Self Ordering: Studi Kasus Implementasi di Restoran Cepat Saji Indonesia - Risko Nur Rizqi; Oktaviano Rifky Ramadhani; M. Hakam Al Kautsar; Ilham Albana (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The Digital transformation in Indonesia’s fast-food industry has accelerated the adoption of self-ordering technology to improve operational efficiency and customer experience. However, the implementation of such systems faces several technical, operational, and social risks that may hinder success. This study aims to analyze the optimization of risk management in the development of self-ordering applications for Indonesian fast-food restaurants. A qualitative approach through a literature review was employed to identify key risk factors and mitigation strategies based on academic sources published between 2020 and 2024. The findings reveal that a comprehensive and contextual risk management approach is critical for successful implementation. Technical risks can be minimized through staged system testing and robust data security, while operational risks can be mitigated through employee training and effective change management. Moreover, adapting system design to local cultural and consumer preferences enhances user acceptance. The study concludes that applying risk management frameworks such as ISO 31000 and PMBOK can strengthen the digital transformation of Indonesia’s fast-food industry and provide practical guidance for decision-makers in managing technology-based restaurant operations.